ANALISIS PERILAKU KELUARGA DAN TENAGA KESEHATAN DALAM PENCEGAHAN PENULARAN COVID-19 PADA BALITA DI DESA POH BERGONG WILAYAH KERJA PUSKESMAS BULELENG III : ANALISIS PERILAKU KELUARGA DAN TENAGA KESEHATAN DALAM PENCEGAHAN PENULARAN COVID-19 PADA BALITA DI DESA POH BERGONG WILAYAH KERJA PUSKESMAS BULELENG III - Espana Giri; Wigutomo Gozali; Ni Komang Sulyastini (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2022)
Maintaining the health of toddlers during the pandemic is the responsibility of families and health workers. In the midst of a pandemic situation, parents continue to work outside the home. The families who are most vulnerable to Covid-19 are toddlers. The study was conducted to analyze the behavior of families and health workers in preventing the transmission of Covid-19 to children. The research was conducted with a cross sectional approach. Research subjects in the family as many as 75 people and as many as 20 health workers. The data was taken by interviewing and filling out questionnaires. Data were analyzed using chi square test. In family behavior, most of them have good behavior as many as 40 people (53.3%), and bad behavior as many as 35 people (46.7%). On the behavior of health workers in providing health services to toddlers who have good behavior as many as 18 people (90%) and who have bad behavior as many as 2 people (10%). Good health behavior is very important in preventing the transmission of Covid-19 in toddlers.